“I use all the free hours I have”: Internet use by Icelandic adolescents and parental restrictions of their use - Sigursteinsdóttir, Hjördís; Halapi, Eva; Ólafsson, Kjartan (Menntavísindasvið Háskóla Íslands, 2015)
During the last decades internet use has increased significantly and constitutes the norm in daily life for most people, especially for adolescents. Recent technical advances have shifted the ability to access the internet from using a desktop computer to being able to access the internet anywhere and anytime by a wireless connection. Adolescence is a period involving substantial physical, cognitive and socio-emotional growth. During this period, the adolescent’s self-image strengthens and inner and outer boundaries are explored, they expand their social networks and spend more time and experience greater intimacy with friends while interactions with their families may be reduced. Adolescents’ everyday life is to a great extent controlled by what can be done online, they communicate and interact socially online, read blogs, browse the internet for knowledge and information, download music and movies. Some find online communication more comfortable than face-to-face interaction, in particular when sharing information pertaining to them. The internet also allows adolescents to connect to friends and relatives living far away. Although most adolescents regard the internet as a necessity in their everyday life, it may also present harm including exposure to sexually explicit content, violence or cyber bullying. Internet use can also become excessive and addictive. A sign of internet addiction has been described as similar to those of addictive gambling. Symptoms include feelings of conflicts of whether spending time online or seeing friends, or attending a sports practice and users gradually withdraw from social interactions outside of the internet. Other signs involve obsessive thoughts about being Online, irritation when online sessions are being interrupted or not possible and some individuals try to conceal the full extent of their internet use. This paper explores online habits and parental restrictions on internet use among 15–16 years old adolescents in Iceland. The paper builds on data from the EU-NET ...